2019
DOI: 10.1016/j.ijbiomac.2018.11.163
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide fractions from Fortunella margarita affect proliferation of Bifidobacterium adolescentis ATCC 15703 and undergo structural changes following fermentation

Abstract: In this study, the relationships between the proliferation effect of polysaccharide fractions from the citrus shrub Fortunella margarita on Bifidobacterium adolescentis ATCC 15703 and their resulting structural changes were investigated. Four polysaccharide fractions, FP20, FP40, FP60, and FP80, were obtained by graded precipitation at ethanol concentrations of 20%, 40%, 60% and 80%, respectively. The results showed that polysaccharide fractions, especially FP20, FP40, and FP60, enhanced the proliferation of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The molecular weights of the fermentation products were determined as described previously (Chen et al, 2019). After fermentation, the culture was centrifuged at 9600g for 20 min to remove the bacteria, then the supernatant was passed through a 0.22 μm water film (Jinteng, Tianjin, China).…”
Section: Determination Of Molecular Weight Of Fermentation Productsmentioning
confidence: 99%
“…The molecular weights of the fermentation products were determined as described previously (Chen et al, 2019). After fermentation, the culture was centrifuged at 9600g for 20 min to remove the bacteria, then the supernatant was passed through a 0.22 μm water film (Jinteng, Tianjin, China).…”
Section: Determination Of Molecular Weight Of Fermentation Productsmentioning
confidence: 99%
“…In addition, other studies have shown that polysaccharide fractions from the citrus shrub, Fortunella margarita , as a carbon source are superior to inulin and glucose in the proliferation of Bifidobacterium . 44 All the above results indicated that polysaccharides can be used as potential prebiotics. Moreover, studies have shown that Bifidobacterium and Lactobacillus not only do not degrade mucin glycoprotein, but also promote the secretion of intestinal mucin glycoprotein, and inhibit the adhesion of harmful bacteria such as Escherichia coli to mucous and intestinal epithelial cells.…”
Section: Resultsmentioning
confidence: 84%
“…The quantification of LA and SCFA profiles in PFM was performed according to the method presented by Chen et al [ 27 ], with some modifications. Determination of lactic, acetic, propionic, and butyric acids was conducted using high-performance liquid chromatography (HPLC).…”
Section: Methodsmentioning
confidence: 99%